State of the Art of Catalysts for Biodiesel Production - Rizwanul Fattah, I. M.; Ong, H. C.; Mahlia, T. M. I.; Mofijur, M.; Silitonga, A. S.; Rahman, S. M. Ashrafur; Ahmad, Arslan (Frontiers in Energy Research, 2020)
Biodiesel is one of the potential alternative energy sources that can be derived from renewable and low-grade origin through different processes. One of the processes is alcoholysis or transesterification in the presence of a suitable catalyst. The catalyst can be either homogeneous or heterogeneous. This article reviews various catalysts used for biodiesel production to date, presents the state of the art of types of catalysts, and compares their suitability and associated challenges in the transesterification process. Biodiesel production using homogeneous and heterogeneous catalysis has been studied extensively, and novel heterogeneous catalysts are being continuously investigated. Homogeneous catalysts are generally efficient in converting biodiesel with low free fatty acid (FFA) and water containing single-origin feedstock. Heterogeneous catalysts, on the other hand, provide superior activity, range of selectivity, good FFA, and water adaptability. The quantity and strengths of active acid or basic sites control these properties. Some of the heterogeneous catalysts such as zirconia and zeolite-based catalysts can be used as both basic and acidic catalyst by suitable alteration. Heterogeneous catalysts from waste and biocatalysts play an essential role in attaining a sustainable alternative to traditional homogeneous catalysts for biodiesel production. Recently, high catalytic efficiency at mild operating conditions has drawn attention to nanocatalysts. This review evaluates state of the art and perspectives for catalytic biodiesel production and assesses the critical operational variables that influence biodiesel production along with the technological solutions for sustainable implementation of the process.